I have a question relating to Propositional Logic. Any help will be greatly appreciated.
Without changing the meaning of the following formulæ, which rely on operator precedence to be interpreted correctly, introduce brackets in each so that no precedence information is required.
(a) $\lnot p \land q \implies r \land p \land q \land \lnot r \iff F$
Ans $((¬p ∧ q) ⇒ (r ∧p )∧(q ∧¬r ))⇔ F$
(b) $¬p ∧ q ∧ r ⇔ ¬p ∨ ¬q ∧¬r$
Ans $(¬p ∧ (q ∧ r)) ⇔ ¬p ∨ (¬q ∧¬r)$
Please can somebody advise me if my answer is correct or incorrect. Thank you all geniuses so much.